Exploring Nutritional Status, Complementary Feeding Quality, and Parenting Styles in Toddlers - Iffah Indri Kusmawati; Angesti Nurgraheni; Ika Sumiyarsi Sukamto; Noviyati Rahardjo Putri; Niken Bayu Argaheni (Postgraduate, University of Mataram, 2025)
This study aimed to describe the nutritional status of toddlers and examine its association with the quality of complementary feeding (MPASI) and caregiver parenting styles in a rural setting. A descriptive observational design was used, involving 93 children aged 6–59 months in the working area of Puskesmas Jenawi, Karanganyar Regency, Central Java. Nutritional status was assessed using WHO weight-for-height z-scores, MPASI quality was determined based on food variety and frequency, and parenting styles were classified into authoritative, authoritarian, indulgent, and uninvolved categories. Results showed that 90.3% of children had normal nutritional status, 6.5% were overweight, 2.2% were wasted, and 1.1% were severely wasted. Half of the toddlers received appropriate MPASI (50.5%), and the most common parenting style was indulgent (32.3%). While this study did not establish statistical associations, children with wasting or severe wasting were more frequently found under authoritarian or uninvolved caregiving styles, suggesting a possible pattern worth further exploration. These findings emphasize the importance of responsive parenting and adequate complementary feeding in promoting child health. The study contributes to science-based educational practices by providing evidence to inform nutrition education and caregiver training programs, particularly in rural communities, where scientific understanding of child nutrition and responsive parenting remains limited.